Role of Nux vomica in Gastrointestinal Disorders – A Case Report (Advancements in Homeopathic Research, 2022)
Gastero intestinal disorders are the more common disorders which we face in day to day life. It needs keen attention in diagnosis and as well as in treatment. Homoeopathy is one of the systems of medicine which brings out permanent cure in both acute and chronic gasterointestinal disorders. There are 10 frequent reasons to consult a physician in gasterology departments of outpatient departments which usually include cystic fibrosis, acid peptic disease (APD), acute hepatitis, recurrent abdominal pain, gastroesophageal reflux disease (GERD), acute diarrhea, chronic diarrhea, upper gastrointestinal bleeding,constipation, and gastrointestinal tract burn.1
Keywords: Nux vomica; Gastrointestinal Disorders; Homoeopathy; GERD; APD